Solid Fluorescence pH Sensors Based on 1,8-Naphthalimide Copolymers Synthesized by UV Curing - Jesús L. Pablos; Esther Hernández; Fernando Catalina; Teresa Corrales (Chemosensors, 2022)
Novel water-swollen photo-crosslinked membranes were obtained by copolymerization of the N-vinylpyrrolidone, butyl acrylate and ethyl methacrylate monomers functionalized with naphthalimide groups, as pH sensitive fluorescence probes. For that purpose, two monomers with pending naphthalimide groups anchored to ethyl methacrylate through alkyl chains with different length, were previously synthesized. The membranes were characterized using different techniques. The pH dependence of absorbance and the corresponding quenching of fluorescence were investigated and related to the structure of naphthalimide substituents linked to the membrane. The new solid sensors exhibited sensitive fluorescence changes at pH < 3, and lower time response was determined for membranes where the sensing group was linked through longer alkyl chain to the polymer matrix. The membranes were solid, thermally stable and easily handled to be applied as sensor materials, and showed a reversible behavior, which is an important feature for further fabrication of an economical on-site tool for the acidity detection in aqueous environments.